The Child’s Right to Establish and Preserve His or Her Identity. Legislative and Case-law Considerations - Cret, Daniela Cristina (Journal of Legal Studies, 2024)
In each state there are certain vulnerable categories of population: children, elderly, disabled people, who need special protection in order to realize their rights. Among them, there are children, whose rights are explicitly regulated in Romania by Law nr. 272/2004 on the protection and promotion of children’s rights, but also in other related laws. In the following, we intend to analyze: the right of the child to establish and preserve his or her identity in accordance with relevant legislation and case law.